View of the Soul in the Jeju Shamanistic Religion as Evident in the Neokdeurim Ritual - Yoo, Yohan (Seoul journal of Korean studies, 2018)
This paper articulates Jeju shamanistic ideas of the human soul. While it has been thought in Jeju that human beings have three or even seven souls, I argue that these numbers are not specific but rather indicate the complete state of the multipart soul. By analyzing the neokdeurim, a Jeju shamanistic ritual performed to reintegrate the human soul, and by referring to related Jeju myths, I demonstrate that Jeju shamanism suggests that every person has a single soul. The soul can be divided into many smaller parts, each of which can depart from the body while the person is living if one meets with a serious accident or is frightened. Parts of the soul that have left the human body do not have independent personalities. Though it is not known where the departed part of the soul goes, it is commonly thought that it wanders around the world. The leaving of a part of the soul is thought to make a person vulnerable to attack by evil spirits and the diseases they bring, though this is not a physical illness itself. It is in order to bring back those departed parts of the soul that the neokdeurim needs to be conducted. KCI Citation Count: 0